Rockburst Prediction From the Perspective of Energy Release: A Case Study of a Diversion Tunnel at Jinping II Hydropower Station - Fan, Yong; Cui, Xianze; Leng, Zhendong; Zheng, Junwei; Wang, Feng; Xu, Xiaole (Frontiers in Earth Science, 2021)
As a man-made engineering hazard, it is widely accepted that rockburst is the result of energy release. Previous studies regarded the unloading of in-situ stress resulted from deep tunnel excavation as a quasi-static process, whereas the transient stress variation during excavation is received much less attention. In this research, rockbursts happened during conduction of diversion tunnels at Jinping II hydropower station were introduced at first. Then, the brittle-ductile-plastic (BDP) transition property of Jinping marble was numerically described by the Hoek-Brown strength criterion, and the dynamic energy release process derived from the transient unloading of in-situ stress was studied using an index, local energy release rate. Studies have shown that, due to transient unloading, the strain energy of the surrounding rock mass goes through a dynamic process of decreasing at first, increasing at second, next reducing and stabilizing at last. Moreover, the first decreasing of strain energy results from elastic unloading wave and does not cause brittle failure in rock masses, which is consistent with the elastic condition. But the secondary reducing of strain energy owes to that the accumulated strain energy in rock masses exceeds the storage limit, and inevitably triggers off the brittle failure in the rock mass. Thus, the shorter distance to tunnel wall means the bigger and intenser energy release. Finally, a relationship between the average value of local energy release rate and the rockburst intensity was established to assess the rockburst risk induced by excavation of a deep tunnel by blasting.